Espaços de cozinhar: mulheres, colonialidade e resistências coletivas a partir do trabalho de cuidado - Luna Esmeraldo Gama Lyra (2021)
The cliché says that "a woman's place is in the kitchen", implying cooking as a private and isolated activity. However, collective and public cooking spaces were and are commonly built and maintained by social movements and various other groups, playing an essential role in food security and community organization. Another infamous and racist expression, "Jane has a foot in the kitchen", is commonly used to impute to someone the condition of servitude, alluding to the domestic work performed by black women during the slavery regime. References to kitchens as a lesser place hide the origins of these spaces of resistance, which date back to the practices of indigenous and African peoples, during the colonial period. The research presented in this dissertation seeks to reconstitute such origins and mobilize the power of collective cooking spaces in the political and affective articulation of women, in contrast to the typically capitalist, colonial, and patriarchal socio-spatial production. Thus, the study comprises two methodological axes: the analysis of historical processes of transformation of the ways of cooking and its spaces in Brazil; and the analysis of narratives of women who today maintain collective kitchens in two urban occupations and an indigenous territory, located respectively in Belo Horizonte-MG, Rio de Janeiro-RJ, and São João das Missões-MG. Historical and current data show that non-colonial and non-white ways of appropriating and experiencing space have been systematically restricted by so-called sanitary or hygienist norms, which are, in fact, sexist and racist. At the same time, such data allow us to conclude that the collectivized care work and the relatively safe spaces that it tends to produce are powerful instruments in the self-organization of women, especially when they are in situations of great vulnerability.